2016
DOI: 10.1186/s13049-016-0287-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the PECARN clinical decision rule for children with minor head trauma: a French multicenter prospective study

Abstract: BackgroundTo date, the Pediatric Emergency Care Applied Research Network (PECARN) rule for identifying children who are at very low risk of clinically-important traumatic brain injuries after minor head trauma has not been validated prospectively in an independent population. Our goal was to evaluate the diagnostic performance of the PECARN clinical decision rule in a French pediatric population in multiple clinical settings.MethodsWe conducted a multicenter, prospective, non-interventional cohort study of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
51
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 22 publications
(26 reference statements)
6
51
2
Order By: Relevance
“…The validation of (PECARN) was not validated in middle east country before. Our study confirmed the good predictive performances of the PECARN clinical decision rule for minor head trauma in children similar to the previous French study [3,4].…”
Section: Methods and Resultssupporting
confidence: 90%
“…The validation of (PECARN) was not validated in middle east country before. Our study confirmed the good predictive performances of the PECARN clinical decision rule for minor head trauma in children similar to the previous French study [3,4].…”
Section: Methods and Resultssupporting
confidence: 90%
“…An earlier retrospective Canadian study showed CTB rates of 6–26% (15% overall). Lower rates have been described in other countries although limited published data are available on interhospital variation . Results from the APHIRST study demonstrate that clinicians at our centres are missing very few significant injuries, suggesting that the imaging rate is not inappropriately low.…”
Section: Discussionmentioning
confidence: 63%
“…Lower rates have been described in other countries although limited published data are available on interhospital variation. 7,[21][22][23][24] Results from the APHIRST study 15,25 demonstrate that clinicians at our centres are missing very few significant injuries, suggesting that the imaging rate is not inappropriately low. Imaging rates were also considerably lower than theoretical imaging rates would be if each of the CDRs examined in APHIRST were applied strictly as a rule, 15 highlighting the importance of considering CDRs as a tool, rather than a rule per se.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the Pediatric Emergency Care Applied Research Network (PECARN) developed two age‐based head trauma prediction rules to identify children at low risk of clinically important traumatic brain injury (ciTBI) who do not require head CT . The PECARN rules were validated in North America and Europe and have since been used to assist CT decision‐making for children with minor head trauma . However, the PECARN rules have not yet been validated in Asia.…”
mentioning
confidence: 99%